Menumbuhkan Interaksi Saling Menghargai melalui Boardgame tentang Nilai-Nilai Budaya Maaf, Tolong, dan Terima Kasih di Kalangan Siswa SD - Agus Wahyudi; Afib Rulyansah; Dewi Widiana Rahayu; Yuanita Syaiful (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop and test the effectiveness of educational board game learning media that integrates politeness values in a fun social game context. Using a quantitative approach with a quasi-experimental non-equivalent control group design, this study involved 60 fourth-grade students from a public elementary school in Surabaya who were divided into an experimental group (using a board game) and a control group (conventional method). Data collection instruments in the form of a Likert scale questionnaire, observation sheets, and supporting interviews were used to measure changes in the use of polite language, willingness to help, and empathetic attitudes. The analysis results showed a significant increase in the experimental group in all indicators of social interaction, in contrast to the control group whose increase was not significant. The data also showed that students were more active, reflective, and emotionally involved during the board game play. This suggests that game-based learning media can be a contextual and effective alternative in character education. This study emphasizes the importance of the experiential learning approach in instilling social values in children, by making learning a fun and meaningful experience. Contextually designed board games not only educate but also build social spaces that stimulate empathy, communication, and the habit of respecting others